Pengaruh Kompensasi, Motivasi, Stres Kerja Dan Lingkungan Kerja Terhadap Kinerja Karyawan Grosir Sembako CV Jembatan Hitam (Studi Pada Karyawan Grosir Sembako CV. Jembatan Hitam, Ganjar Asri, Kota Metro) - Ayuningtias, Icha; Suryadi, Suryadi (Jurnal Manajemen DIVERSIFIKASI, 2022)
ABSTRACT The most important asset for an organization is human resources so that every company or organization must work together optimally to produce quality products. Where the management is required to use a good management system and can be used as a tool to improve the performance of its employees. The formulation of the problem in this study was "Whether compensation, motivation, work stress and work environment have a partial or simultaneous effect on the performance of employees at CV Jembatan Hitam wholesalers". From these problems, the purpose of this study was to determine the effect of compensation, motivation, work stress, work environment and employee performance at CV Jembatan Hitam. This research method was quantitative. Data collection techniques were carried out using a questionnaire. Samples were taken as many as 40 respondents with saturated sample technique. The data obtained are then processed using SPSS version 22. Based on data analysis using SPSS, the conclusions in this study were that between compensation, motivation, work stress, and work environment only compensation, motivation, and work environment had a positive and significant effect on employee performance, while simultaneously compensation, motivation, work stress and work environment had a positive and significant effect on employee performance simultaneously. Keywords: Compensation, Motivation, Work Stress, Work Environment, Employee Performance